2013
DOI: 10.1111/ele.12127
|View full text |Cite
|
Sign up to set email alerts
|

An empirical assessment of tree branching networks and implications for plant allometric scaling models

Abstract: Several theories predict whole-tree function on the basis of allometric scaling relationships assumed to emerge from traits of branching networks. To test this key assumption, and more generally, to explore patterns of external architecture within and across trees, we measure branch traits (radii/lengths) and calculate scaling exponents from five functionally divergent species. Consistent with leading theories, including metabolic scaling theory, branching is area preserving and statistically self-similar with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(137 citation statements)
references
References 52 publications
(102 reference statements)
13
110
1
1
Order By: Relevance
“…There is also no consensus if there is a scientific basis to use any fixed exponent across all age groups even though in many instances there are several allometric exponents embedded within these age groups (4). Recent studies by many investigators have shown that the concept of quarter-power law or so-called theoretical allometry (fixed exponents of 0.25, 0.75, or 1.0) is incorrect (43)(44)(45)(46)(47)(48)(49)(50)(51). The exponents of allometry for drug clearance in preterm and term neonates are generally >1 (4,(8)(9)(10)(11)39).…”
Section: Discussionmentioning
confidence: 99%
“…There is also no consensus if there is a scientific basis to use any fixed exponent across all age groups even though in many instances there are several allometric exponents embedded within these age groups (4). Recent studies by many investigators have shown that the concept of quarter-power law or so-called theoretical allometry (fixed exponents of 0.25, 0.75, or 1.0) is incorrect (43)(44)(45)(46)(47)(48)(49)(50)(51). The exponents of allometry for drug clearance in preterm and term neonates are generally >1 (4,(8)(9)(10)(11)39).…”
Section: Discussionmentioning
confidence: 99%
“…The observation by Leonardo da Vinci that "all branches of a tree at every stage of its height when put together are equal in thickness to the trunk" (Richter 1888) has been interpreted as a feature of the tree's water transport system (Hari et al 1986), or as response to wind-induced stresses (Eloy 2011). In any case, there is a very strong relationship between the cross-sectional area of the tree stem at a point and the sum of the cross-sectional area of branches above that point (Hari et al 1986, Bentley et al 2013. A cumulative branch area constraint would ensure realistic branch amounts at the tree level, although climatic variation in the branchwood area to stemwood area ratio must be taken into account (Berninger et al 1995).…”
Section: Progress In Predicting Mbd From Crown Characteristicsmentioning
confidence: 99%
“…This is because small plants (e.g. herbs) lack some key features of trees: high stature, branching networks with a large number of branchings121314, and large amounts of secondary xylem15. For instance, for small plants MST predicted that (Table 1): H (height) ∝  D (Diameter), M L (leaf mass) ∝  M S (stem mass), M A (aboveground mass) ∝  D 3 and M A  ∝  H 3 (for details, see Appendix 1).…”
mentioning
confidence: 99%